STYLISTICS FEATURES ON TELEVISION ADVERTISEMENT ABOUT MEN TREATMENT - Kusumah, Cita (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2024)
Advertisement is one of the communication tools used to deliver messages, ideas, and advice, and sometimes it offers the product or service in order to make people interested in buying and using it. One of the advertisements is about treatment that is usually used by women and is identical with women, but nowadays men also need some kinds of treatment like that. In this paper, we intend to discuss the men's treatment advertisements on television. Some ways that we can see from these advertisements are the language styles that appear on the advertisement as the form of information utterance and the ways to get the interests of men to try and buy it, so that this advertisement uses special language styles. In this paper, we use the stylistics approach to analyze the television advertisements on men's treatment. The research methods are qualitative and descriptive. First, we search for valid data, then we describe the data based on the theory, and lastly, we analyze the data. The result of the research shows that phonological, lexical, syntactic, semantic, and morphological features occur in men’s treatment advertisements. The semantic features appear more intensely in the advertisements, especially the personification form and the morphological features in the form of affixation. There are some words that exaggerate their meanings. They use these kinds of stylistic features because they want to persuade consumers to buy the products.